In-Between: Wrocław’s Jewish Community and Claims of ModernityReligion and Power. Problem of American Theocracies - Jasnowski, Paweł (Studia religiologica, 2017)
Review: Agata Rybińska, Granice integracji. Religijność Żydów wrocławskichw drugiej połowie XIX wieku (1854–1890) (“The Limits of Integration. Religiousness of the Breslau Jews in the Second Half of the Nineteenth Century (1854–1890)”), Wydawnictwo Uniwersytetu Wrocławskiego, Wrocław 2017, 264 pp.